In situ characterisation of phytohormones from wounded Arabidopsis leaves using desorption electrospray ionisation mass spectrometry imaging - Zhang, Chao; Žukauskaitė, Asta; Petřík, Ivan; Pěnčík, Aleš; Hönig, Martin; Grúz, Jiří; Široká, Jitka; Novák, Ondřej; DoleŽal, Karel (The Analyst, 2021)
Phytohormones (plant hormones) are a group of small signalling molecules that act as important endogenous regulators in plant development and stress responses. Previous research has identified the phytohormone species, jasmonates, auxins and abscisic acid, and their related compounds in stressed leaf extracts. However, in situ visualisations of endogenous phytohormones from intact plant tissues remain elusive without the usage of labels or reporters. Mass spectrometry imaging is a label-free analytical technique that has been successfully applied for the direct detection of plant proteins, lipids, carbohydrates and many other biomolecules. In this study, desorption electrospray ionisation mass spectrometry imaging (DESI-MSI) was used for high throughput visualisation and evaluation of wound-induced phytohormones inside Arabidopsis thaliana leaves. The results showed higher levels of jasmonates, salicylic acid, abscisic acid and indole-3-acetic acid in their ion intensity maps established from wounded leaves compared to control leaves, which have been validated in the parallel liquid chromatography-mass spectrometry quantification, and the untainted distributions of the identified phytohormones in leaves were confirmed by mass spectrometry imaging of instant leaf imprinted thin-layer chromatography plate samples. Further statistical analysis has not only demonstrated a significant increase of jasmonic acid and its precursor compounds in wounded leaves/regions but also highlighted a potential correlation in different phytohormone species. Our results suggest that DESI-MSI can be used to in situ characterise multiple phytohormone compounds from intact leaves with 200 μm spatial resolution to provide insight into phytohormone distributions in wounded leaves, along with their correlated precursors and metabolites under mechanical stress.
Keywords: tandemová hmotnostní spektrometrie; Abscisic Acid; regulátory růstu rostlin; Plant Leaves; Tandem Mass Spectrometry; listy rostlin; kyselina abscisová; Spectrometry, Mass, Electrospray Ionization; hmotnostní spektrometrie s elektrosprejovou ionizací; Plant Growth Regulators; Arabidopsis